2020
DOI: 10.1002/cam4.2855
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16 and HPV E4 on biopsy samples and methylation of FAM19A4 and miR124‐2 on cervical cytology samples in the classification of cervical squamous intraepithelial lesions

Abstract: The decision to treat a cervical squamous intraepithelial lesion (SIL) by loop electrosurgical excision procedure (LEEP) relies heavily on a colposcopy‐directed biopsy showing high‐grade (H)SIL. Diagnosis is often supported by p16, an immunohistochemical (IHC) biomarker of high‐risk (hr)HPV E7 gene activity. Additional potential markers include methylation of tumor suppressor genes FAM19A4/miR124‐2 in cervical cytology for advanced transforming HSIL and the IHC marker HPV E4 for productive, potentially regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…36 However, Leeman et al found 3% positive E4 staining in CIN3. 29 We showed that in a small number of CIN3 lesions (9.8%; 23/235) and IS 5-6 lesions (12.0%; 38/316), E4 positivity was found, which is in agreement with our earlier findings. 20 Moreover, we now extend these findings by showing that methylation was present in 60.9% (14/23) of E4-positive CIN3 and in 65.8% (25/38) of E4-positive IS 5-6 lesions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…36 However, Leeman et al found 3% positive E4 staining in CIN3. 29 We showed that in a small number of CIN3 lesions (9.8%; 23/235) and IS 5-6 lesions (12.0%; 38/316), E4 positivity was found, which is in agreement with our earlier findings. 20 Moreover, we now extend these findings by showing that methylation was present in 60.9% (14/23) of E4-positive CIN3 and in 65.8% (25/38) of E4-positive IS 5-6 lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of this study, we stratified all CIN2/3 lesions according to the immunoscore and methylation status into biomarker profiles (Table 4). E4 expression was not used in these biomarker 20,29,36 and the presence of E4 in a minority of methylation-positive CIN2/3, makes the potential clinical significance of absence or presence of E4 expression difficult to interpret in terms of regression or progression. Methylation status was included since methylation levels increase with increasing disease severity and are extremely high in cervical carcinomas (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Griffin et al compared the expression of E4 to p16 INK4A , another host marker, and the hypermethylation of some hostcell genes, which increases with CIN severity. They claim that E4 expression is correlated with low hypermethylation and the absence of p16 INK4A , which is not observed in cervical carcinoma, as described in additional studies [7,96,97].…”
Section: Viral E4 Proteinmentioning
confidence: 90%
“…HPVs are non-enveloped small DNA viruses that widely exist in nature and encompass a large family of viruses, both benign and highly carcinogenic (4). HPVs primarily replicate on the surface of squamous epithelia, such as at the junction of squamous epithelial cells and the columnar epithelium of the cervix; this viral replication can interfere with the normal replication of squamous cells, leading to abnormal proliferation of the squamous epithelia (5). Generally, as a non-lytic infection, this process does not result in a strong immune response or inflammation by activating Toll-like receptors and natural killer cells (6).…”
Section: Introductionmentioning
confidence: 99%